Hackers Wanted - Libicki, Martin C.; Senty, David; Pollak, Julia (RAND Corporation, 2023)
The perceived shortage of cybersecurity professionals working on national security may endanger the nation’s networks and be a disadvantage in cyberspace conflict. RAND examined the cybersecurity labor market, especially in regard to national defense. Analysis suggests market forces and government programs will draw more workers into the profession in time, and steps taken today would not bear fruit for another five to ten years.